2023
DOI: 10.48088/ejg.m.bat.14.4.022.036
|View full text |Cite
|
Sign up to set email alerts
|

PoD: A Web Tool for Population Downscaling Using Areal Interpolation and Volunteered Geographic Information

Marios Batsaris,
Sofia Zafeirelli,
Michail Vaitis
et al.

Abstract: Population data are commonly sourced from censuses, and to meet confidentiality requirements, they are spatially aggregated into standardized enumeration units. However, the need often arises to transform such datasets into user-defined spatial scales, a process known as areal interpolation. Areal interpolation is the process of data transformation across spatial zones and is particularly suitable for aggregated data such as census data. While numerous areal interpolation methods exist, a lack of implementatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…The two accessibility indicators have been calculated for the three years based on the respective transport infrastructure and population. Population data play a crucial role in numerous studies, and typically, as demonstrated in this research, they are sourced from census surveys (Batsaris et al, 2023). Importantly, population has not been used directly as a factor in the accessibility indices but as a proxy for the attractiveness of destinations in both indicators.…”
Section: Relation Of Accessibility and Depopulationmentioning
confidence: 99%
“…The two accessibility indicators have been calculated for the three years based on the respective transport infrastructure and population. Population data play a crucial role in numerous studies, and typically, as demonstrated in this research, they are sourced from census surveys (Batsaris et al, 2023). Importantly, population has not been used directly as a factor in the accessibility indices but as a proxy for the attractiveness of destinations in both indicators.…”
Section: Relation Of Accessibility and Depopulationmentioning
confidence: 99%